2022
DOI: 10.3390/pr10081628
|View full text |Cite
|
Sign up to set email alerts
|

Research on Energy Loss Characteristics of Pump-Turbine during Abnormal Shutdown

Abstract: Pumped-storage hydropower (PSH) stations are an efficient emission-free technology to balance renewable energy generation instabilities. The pump-turbine is a core component of PSH stations requiring frequent start-up, shutdown, and working conditions for regulation tasks, making it prone to instabilities. Based on entropy production theory and vortex dynamics, we analyzed the energy loss characteristics for three working conditions of the pump, pump brake, and turbine when shutting down the pump-turbine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Authors in (Lain and Mejia, 2022) claim that physical modelling have gradually been replaced by CFD modelling techniques which are used to study hydro-kinetic along with hydro-dynamic studies. With the increasing popularity of PSH as energy storage elements and a good ancillary service provider for electric grid, CFD simulation of model turbine as a pump has been performed in (Deng et al, 2022) to quantify energy loss and entropy generation. Furthermore, studies about change in guide vane air foil on the flow characteristics of draft tube for improvement of energy recovery, vibrations intensity, stable operation of turbine, design methods of multiphase pumps for hydrodynamic and structural points of view, etc.…”
Section: 2mentioning
confidence: 99%
“…Authors in (Lain and Mejia, 2022) claim that physical modelling have gradually been replaced by CFD modelling techniques which are used to study hydro-kinetic along with hydro-dynamic studies. With the increasing popularity of PSH as energy storage elements and a good ancillary service provider for electric grid, CFD simulation of model turbine as a pump has been performed in (Deng et al, 2022) to quantify energy loss and entropy generation. Furthermore, studies about change in guide vane air foil on the flow characteristics of draft tube for improvement of energy recovery, vibrations intensity, stable operation of turbine, design methods of multiphase pumps for hydrodynamic and structural points of view, etc.…”
Section: 2mentioning
confidence: 99%
“…However, the lack of a method to analyze the flow pattern of the FFP under the shutdown transition makes it difficult. It is worth noting that the structure of the FFP is similar to those of the other hydraulic machines [12,13], such as the AFPs [14,15], the turbines [16][17][18], and the centrifugal pumps [19][20][21][22][23][24]. The performance of these hydraulic machines during shutdown transition has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the energy loss was mainly concentrated in the impeller wake and the bladeless space. Deng et al 19 investigated the energy loss characteristics during the abnormal shutdown of a T-type pumping storage station. The results showed that the entropy production and vortex volume originated from the transition of the guide vane through the leafless space to the runner.…”
Section: Introductionmentioning
confidence: 99%